MODEL PENGHITUNGAN TARIF PREMI ASURANSI SYARIAH DALAM HUBUNGANNYA DENGAN SEGMENTASI PASAR DAN LABA PERUSAHAAN - Ella Patriana (Faculty of Economic and Business, 2014)
The research aims to analyze the model calculations sharia insurance premium rates for savings products and not saving in connection with market segmentation and company profit. The method used in this research is descriptive qualitative. In accordance with the characteristics of the product, for a savings element that has a market segmentation leads to the individual, while that does not have a savings element, it would be appropriate is marketed to a collection or company. Companies with on investment high return using a relatively small debt. High rate of return allowed them to finance the majority of their funding needs with funds generated from internal activities.DOI: 10.15408/etk.v13i2.1885